Harmonic Balance Solution Of Coupled Nonlinear Non-Conservative Differential Equation - Rahman, M Saifur; Rahman, M Majedur; Rahaman, M Sajedur; Alam, M Shamsul (GANIT: Journal of Bangladesh Mathematical Society, 2013)
A modified harmonic balance method is employed to determine the second approximate solutions to a coupled nonlinear differential equation near the limit cycle. The solution shows a good agreement with the numerical solution. DOI: http://dx.doi.org/10.3329/ganit.v32i0.13640 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 32 (2012) 1 14